A Novel Approach to Real Time Face Detection and Recognition - Parihar, Vikramsingh R; Dhote, Anagha P (International Journal of Computer Sciences and Engineering, 2025)
The proposed approach represents novel and simple model approach based on a mixture of techniques and algorithms in a shared pool based on Viola–Jones object detection framework algorithm combined with geometric and symmetric information of the face parts from the image in a smart algorithm. The study is a continued part of previous work, the proposed model is modestly applied with hundreds of face images taken under different lighting conditions, a number of general assumptions used in this research field are identified. The proposed algorithm goes beyond the limits of all existing technologies as it obtains the unique functional features by enabling the proposed model to work with different skin color tone, applying it to low-quality images, detecting faces with eye glasses, determining the position of facial parts (e.g. eye pupils, nose, lips, etc.) and detect several faces on one image is typically designed to deal with single images.